1998
DOI: 10.1038/sj.bmt.1701437
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases and autoimmunity post-bone marrow transplantation

Abstract: BMT can both transmit and eliminate autoimmune diseases, and hence it has been suggested as an optional treatment for severe autoimmune conditions. In this communication we deal with the question of whether chronic GVHD is an autoimmune disease in itself, review the literature reports of autoimmune diseases following BMT in humans, and describe the autoimmune nature of the post-BMT state. Chronic GVHD, which is a frequent complication post-BMT, has clinical and pathogenic characteristics similar to autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
153
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 64 publications
3
153
2
1
Order By: Relevance
“…The cutaneous lesions of psoriasis are characterized by a hyperproliferation of keratinocytes in the epidermis, and it has been suggested that activated T cells play an important role in the disease's pathogenesis. In allogeneic bone marrow transplantation (BMT), the immune system of the host is effectively eliminated by a pre-conditioning regimen, and immunity after BMT is mostly of donor origin [3]. Therefore, it has been suspected that the course of autoimmune disease can be modified by allogeneic BMT.…”
Section: Introductionmentioning
confidence: 99%
“…The cutaneous lesions of psoriasis are characterized by a hyperproliferation of keratinocytes in the epidermis, and it has been suggested that activated T cells play an important role in the disease's pathogenesis. In allogeneic bone marrow transplantation (BMT), the immune system of the host is effectively eliminated by a pre-conditioning regimen, and immunity after BMT is mostly of donor origin [3]. Therefore, it has been suspected that the course of autoimmune disease can be modified by allogeneic BMT.…”
Section: Introductionmentioning
confidence: 99%
“…1 Post transplant, PRCA is usually a complication of major ABO incompatibility and may have an increased incidence after nonmyeloablative compared with myeloablative conditioning regimens. 2 While autoimmune haematological disorders including haemolytic anaemia and immune neutropenia, thrombocytopenia and pancytopenia due to peripheral destruction are well recognised post allograft, 3 often in the context of chronic graft versus host disease (GVHD), 4 to our knowledge PRCA as an immune complication in the absence of ABO incompatibility has not been reported. This case documents PRCA after an ABO-compatible nonmyeloablative allograft in the absence of any secondary causes.…”
mentioning
confidence: 99%
“…Thus, it is likely that the course of autoimmune disorders can be modified by allogeneic BMT. 7 Atopic dermatitis is thought to be an autoimmune or allergic disease, as indicated by increasing evidence for the role of a cellular immune reaction in the pathogenesis. 1,2 In the present case, the immunosuppressive treatment used to prevent GVHD may have also influenced the clinical course of the atopic dermatitis.…”
mentioning
confidence: 99%